2005
DOI: 10.1177/0193945905275973
|View full text |Cite
|
Sign up to set email alerts
|

Self-Care of Women Growing Older With HIV and/or AIDS

Abstract: The purpose of this report is to describe the ways older women living with HIV perceive of and practice self-care. Data are taken from a culturally diverse subsample of 9 women age 50 years or older who participated in a larger longitudinal qualitative study of women who were HIV infected. During a period of 2 years, 10 semistructured narrative interviews were conducted with each of the 9 participants to gain an in-depth understanding of their experiences with symptom management, adherence to medical regimens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 49 publications
0
37
1
Order By: Relevance
“…In contrast to the participants in the current study, Plach et al's (2005) participants were much older and were not caregivers for their children. Therefore, being able to focus solely on themselves most likely contributed to those participants' ability to shift their illness perspective to take care of themselves and to remain proactive with their health.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In contrast to the participants in the current study, Plach et al's (2005) participants were much older and were not caregivers for their children. Therefore, being able to focus solely on themselves most likely contributed to those participants' ability to shift their illness perspective to take care of themselves and to remain proactive with their health.…”
Section: Discussioncontrasting
confidence: 58%
“…Similarly, active meaning-making strategies identified in the current study were compared with the coping strategy of changing ways of thinking identified in a study by Plach, Stevens, and Keigher (2005), who drew upon the illness experiences of a sample of older White, African American, and Hispanic HIVinfected women who changed their thinking about life, death, sickness, and health by adopting more positive attitudes and by focusing on their previously neglected physical and emotional needs. In contrast to the participants in the current study, Plach et al's (2005) participants were much older and were not caregivers for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Research, however, is emerging that recognizes how age is an important social factor to consider when examining the HIV self-management behaviors of HIV-positive women. Plach et al 19 conducted in-depth interviews with nine culturally diverse HIV-positive women ages 50-56. They report that women's definitions of HIV self-management are shaped in large part by their life experiences over time, which serve as a buffer for managing the health effects of HIV.…”
Section: Chronic Illness Self-managementmentioning
confidence: 99%
“…As noted by Plach et al, women viewed their advanced age to be a source of wisdom from which they could rely upon to cope with chronic illness as well as life challenges. 19 That is, older women with HIV have a lifetime of self-management experiences from which to draw. Ultimately, they purport that mature age is viewed as a strength to simultaneously managing HIV and other co-morbid conditions.…”
Section: Chronic Illness Self-managementmentioning
confidence: 99%
“…Although many studies have been conducted with HIV-infected women, few focus on mature women living with HIV, particularly Midwestern women (Gosselink & Myllykangas, 2007;Plach, Stevens, & Keigher, 2005). Much of the available literature about the population of mature women living with HIV focuses on menopausal issues (Arnsten et al, 2006;Fantry, Zhan, Taylor, Sill, & Flaws, 2005;Santoro, Arnsten, Buono, Hoard, & Schoenbaum, 2005;Schoenbaum et al, 2005), with less attention to other unique health concerns as perceived by the population.…”
Section: Discussionmentioning
confidence: 99%